ZnO nanowires based degradable high-performance photodetectors for eco-friendly green electronics - Yalagala, Bhavani Prasad; Dahiya, Abhishek Singh; Dahiya, Ravinder (Opto-Electronic Advances, 2023)
Disposable devices designed for single and/or multiple reliable measurements over a short duration have attracted considerable interest recently. However, these devices often use non-recyclable and non-biodegradable materials and wasteful fabrication methods. Herein, we present ZnO nanowires (NWs) based degradable high-performance UV photodetectors (PDs) on flexible chitosan substrate. Systematic investigations reveal the presented device exhibits excellent photo response, including high responsivity (55 A/W), superior specific detectivity (4x1014 jones), and the highest gain (8.5x1010) among the reported state of the art biodegradable PDs. Further, the presented PDs display excellent mechanical flexibility under wide range of bending conditions and thermal stability in the measured temperature range (5–50 °C). The biodegradability studies performed on the device, in both deionized (DI) water (pH≈6) and PBS solution (pH=7.4), show fast degradability in DI water (20 mins) as compared to PBS (48 h). These results show the potential the presented approach holds for green and cost-effective fabrication of wearable, and disposable sensing systems with reduced adverse environmental impact.